Path planning and optimization for micro-robot in a vessel-mimic environment - Huan, Zhijie; Ma, Weicheng; Wang, Jiamin; Wu, Feibin (Frontiers in Neurorobotics, 2022)
Manipulating micro-robots in blood vessels is an essential technical method for researchers in medical applications such as drug delivery and thrombus removal. The usage of micro-robots in the field of medical treatment can break through the limitations of many traditional clinical methods. In this paper, we aim to make the micro-robot more intelligent while moving in blood vessels. First, as we obtained the image of the blood vessels, skeleton of the image was extracted which was further be used for path planning. Then, skeleton-extraction based A* algorithm was used for searching a best route for the movement of microrobot with safety distance away from the vascular wall. Finally, gradient descent algorithm was utilized to smooth the planned path. Simulations were conducted to verify effectiveness of the proposed algorithms. The proposed methods would improve efficiency for further manipulation of micro-robot in blood vessel environment.